Silvopastoral Systems in the Aysen and Magallanes Regions of the Chilean Patagonia - Sotomayor, Alvaro; Schmidt, Harald; Salinas, Jaime; Schmidt, Andreas; Sanchez Jardon, Laura; Alonso, Maximo; Moya, Ivan; Teuber, Osvaldo (My University, 2016)
This chapter presents the experiences with silvopastoral systems and windbreaks in the Aysen region, located in the extreme south of Chile. These systems include the native tree species of the genus Nothofagus and other cold-tolerant tree species such as Pinus contorta, Pinus ponderosa and Pseudotsuga menziesii that were introduced in the 1960 from regions of the United States and Canada, where the weather conditions are similar to those of the Patagonian Region of Chile. The experience so far shows that the establishment of trees in silvopastoral systems and windbreaks has helped improve prairies productivity and therefore animal production, and provided wood for industrial purposes and farm needs. The factor that most influenced increase in prairie productivity in silvopastoral systems was tree crown coverage, which reduced the wind speed by 200 %. The use of windbreaks in this region demonstrated the importance of these systems in farm properties, especially in open areas without any protection, where productivity of different fodder species increased by 47 % in the most protected zone of 0-5 H (where H is the height of the windbreak tree) to 14 % in the least protected zone (15 H). In addition, because of wind reduction by windbreak and trees established in silvopastoral systems arrangement, and management of native forests for this purpose, would reduce soil erosion which is a major problem in the Patagonian region of Chile.
Keywords: windbreaks; pinus contorta; dactilys glomerata; nothofagus antarctica; nothofagus pumilio